Influence of fuel properties on internal nozzle flow development in a multi-hole diesel injector. (15th September 2017) - Torelli, Roberto; Som, Sibendu; Pei, Yuanjiang; Zhang, Yu; Traver, Michael
Highlights: Gasoline-like fuels have been compared against n-Dodecane in CFD simulations of internal nozzle flows. Fuels' physical properties influence the injector performance and the occurrence and magnitude of cavitation. In-and off-axis needle motions are responsible for internal nozzle flow structures occurrence. Extension, duration, and timing of internal structures are affected by the fuel properties. Fuels' response to several operating conditions and geometry features has been evaluated. At very low needle lifts, the use of gasoline-like fuels promoted the occurrence of cavitation at the needle seat. The extension of cavitation occurrence has been shown to correlate with the orifice cross-sectional area. Abstract: Fuel physical properties are known to influence in-nozzle flow behavior, in turn affecting spray formation in internal combustion engines. A series of 3D simulations was performed to model the internal nozzle flow in a five-hole mini-sac diesel injector. The goal of the study was to evaluate the behavior of two gasoline-like fuels (full-range naphtha and light naphtha) and compare them against n-Dodecane, selected from a palette used as a diesel surrogate. Simulations were carried out using a multi-phase flow representation based on the mixture model assumption with the Volume of Fluid (VOF) method, and including cavitation effects by means of the Homogeneous Relaxation Model (HRM). Validated methodologies from our previous studies were employed to account for full needle motion. Detailed simulations revealed the influence of the fuel properties on injector performance, injected fuel energy and propensity to cavitation. The three fuels were compared with respect to global parameters such as mass flow rate and area contraction coefficients, and local parameters such as pressure and velocity distribution inside the sac and orifices. Parametric investigations were also performed to understand the fuel response to changes in the fuel injection temperature, injection pressure, and geometry details. Cavitation magnitude was observed to be strongly associated with the values of saturation pressure. Owing to their higher volatility, the two gasoline-like fuels were observed to cavitate more than n-Dodecane across all the investigated conditions. While at full needle lift cavitation was reduced for all fuels, during the injection transients the gasoline-like fuels showed more propensity to cavitate inside the orifice and seat regions. This is expected to have a profound influence on nozzle erosion. Although full-range and light naphtha have lower densities compared to n-Dodecane, owing to their lower viscosity, the mass flow rate differences between the naphtha fuels and n-Dodecane were small. The analysis of fuel energy content showed that the higher lower heating value (LHV) of light naphtha helped compensate for the slightly lower total delivered mass.